Semen cryopreservation protocols of Mangalarga Marchador stallions - Candeias, Marcela Leite; Alvarenga, Marco Antonio [UNESP]; Carmo, Márcio Teoro do [UNESP]; Ferreira, Heder Nunes [UNESP]; Maior, Mônica Russo Souto; Torres Filho, Rodolpho de Almeida; Rodrigues, André Luís Rios; Brandão, Felipe Zandonadi (Sociedade Brasileira de Zootecnia, 2012)
The effect of the utilization of three semen protocols (Inra 82®, Merck Gema and Botu-crio®) and two filling techniques (0.25 and 0.50 mL straws) in Mangalarga Marchador stallions were studied in this experiment. Sperm parameters were assessed during processing and post-freezing. No interactions between the protocols and type of filling were observed, so they were assessed separately. Sperm parameters were not altered when the extender was added to the centrifugation; however, there was reduction of motility and strength when freezing extenders were added. The Botu-crio® protocol preserved the parameters of total and progressive sperm motility, smoothed path velocity (µm/s), straight line velocity (µm/s), track velocity (µm/s) and the average and fast spermatozoa percentage better than the others. No difference between the extenders for the percentage of sperm integrity was observed. There was no difference in the responses studied on the filling techniques. The stallions presented better freezing with the use of the Botu-crio® protocol. The best post-freezing viability results were found for semen frozen using the Botu-crio® protocol and there were no differences concerning the sperm quality comparing 0.25 and 0.50 mL straws.
Keywords: ejaculated; equine; extender; straw